Race, market size, segregation and subsequent opportunities for former NFL head coaches - Jeremy J. Foreman; Robert M. Turick; Dylan P. Williams; Tyler L. Skinner (Journal of Economics and Statistics, 2024)
This study examines subsequent head coach opportunities for former National Football League (NFL) head coaches. Under a subsequent CEO career framework, survival analysis is used to examine the effects of race and market characteristics on subsequent NFL head coach opportunities for former head coaches. Observations of former head coaches who neither ended their coaching careers nor possess head coach positions in the observed seasons are used ( n = 1,132). Black former NFL head coaches are less likely to secure subsequent NFL head coaching opportunities if their most recent coaching position was in a large media market. However, both Black and non-Black former head coaches who most recently coached in highly segregated metropolitan areas experienced higher likelihoods of securing subsequent head coaching opportunities. This segregated market effect is even stronger for Black former head coaches. The NFL can utilize this information in policy formation decisions regarding hiring policies and practices. Teams and their lead executives can also use this information to identify any personal biases that may arise within the head coach labor market. Coaches may use the information to best position themselves for subsequent career opportunities.
Keywords: Z; L83; 330; discrimination; executives; head coaches; labor market; National Football League